The Participatory Journalism of Michael Herr, Norman Mailer, Hunter S. Thompson, and Joan Didion : Creating New Reporting Styles. - Mosser, Jason (Lewiston : Edwin Mellen Press, 2011)
Among New Journalists of the 1960s-1970s, Michael Herr, Norman Mailer, Hunter S. Thompson, and Joan Didion approached their subjects by placing themselves in the center of their narratives as protagonists and by openly acknowledging their subjective impressions of the events they reported. Unlike journalists who adopted the conventions of detachment and objectivity, these New Journalists employed their subjective, literary styles to construct their narrative personae and to dramatize not only the events like the Vietnam War and the 1972 presidential campaign but their direct participation in t.
Cover Page; Title Page; Dedication; Table of Contents; Preface; Acknowledgements; Chapter One: Participatory New Journalism; Chapter Two: Michael Herr's Dispatches: Journalist as Hipster and Postmodern Hero; Chapter Three: Norman Mailer's The Armies of the Night: Journalist as Novelist and Intellectual; Chapter Four: Hunter S. Thompson's Fear and Loathing: On the Campaign Trail '72 Journalist as Prankster and Prophet; Chapter Five: Joan Didion's Salvador and Miami: Journalist as Witness and Oracle; Bibliography; Index
Print version record.
English.
eBooks on EBSCOhost
Keywords: Herr, Michael -- Criticism and interpretation; Mailer, Norman -- Criticism and interpretation; Thompson, Hunter S. -- Criticism and interpretation; Didion, Joan -- Criticism and interpretation; Didion, Joan; Herr, Michael; Mailer, Norman; Thompson, Hunter S; Reportage literature, American -- History and criticism; American prose literature -- History and criticism -- 20th century; Journalism -- United States -- History -- 20th century; Littérature de reportage américaine -- Histoire et critique; Prose américaine -- Histoire et critique -- 20e siècle.; LITERARY CRITICISM -- American -- General; American prose literature; Journalism; Reportage literature, American; United States; English; Languages & Literatures; American Literature; 1900-1999; Criticism, interpretation, etc; History